Down-Selection and Outdoor Evaluation of Novel, Halotolerant Algal Strains for Winter Cultivation - Dahlin, Lukas R.; Van Wychen, Stefanie; Gerken, Henri G.; McGowen, John; Pienkos, Philip T.; Posewitz, Matthew C.; Guarnieri, Michael T. (Frontiers in Plant Science, 2018)
Algae offer promising feedstocks for the production of renewable fuel and chemical intermediates. However, at present, poor outdoor winter cultivation capacity limits deployment potential. In this study, 300 distinct algal strains were screened in saline media for their cultivation suitability during winter conditions in Mesa, Arizona. Three down-selected strains were chosen following laboratory evaluations and grown outdoors in 1000 L raceway ponds during the winter. Algal biomass productivity and compositional analysis for lipids and carbohydrates show successful outdoor deployment and cultivation under winter conditions for these strains. Outdoor harvest-yield biomass productivities ranged from 2.9 to 4.0 g/m2/day over an 18-day winter cultivation trial, with maximum productivities ranging from 4.0 to 6.5 g/m2/day, the highest productivities reported to date for algal winter strains grown in saline media in open raceway ponds. Peak fatty acid levels ranged from 9% to 26% percent of biomass, and peak carbohydrate levels ranged from 13% to 34% depending on the strain. Changes in the lipid and carbohydrate profile throughout outdoor growth are reported. This study demonstrates that algal strain screening under simulated outdoor environmental conditions in the laboratory enables identification of strains with robust biomass productivity and biofuel precursor composition. The strains isolated here represent promising winter deployment candidates for seasonal algal biomass production when using crop rotation strategies.